Implementation of a surgical handover tool in a busy tertiary referral centre: a complete audit cycle. (February 2016) - Gibbons, J.; Nugent, E.; Tierney, S.; Kavanagh, D.
Abstract Background The implementation of the European work-time directive has created increased transitions of care during weekends as doctors adhere to a shift-work structure. This raises concerns over continuity of care and patient safety. To address this, doctors must develop a time efficient yet safe system of handover of patients to the team on-call. Intuitively weekend care provides the ideal setting to develop a handover tool. Aim To develop and implement a process of surgical handover and to improve weekend discharge rate on a surgical service. Methods Data was collected at three time-points over a 6 months period (October 2013–March 2014) encompassing development, implementation, re-evaluation and modification of the handover process. The outcomes measured were: number of inpatients, number of weekend discharges, length of stay (LOS) of inpatients recorded for the four weekends within the month, and total emergency response team (ERT) calls each month. Results Mean number of included patients each month was 294 (σ = 14). Following the introduction of weekend handover there was a 40 % increase in weekend discharges which was consistent for subsequent time-points (p < 0.05). Following the second intervention there was a statistically significant reduction in mean LOS from 13 to 5.4 days (p < 0.05) and the total number of ERT calls for the month reduced from 12 to 4 (p < 0.05). Conclusions The standardisation of weekend handover using a combination of an electronic tool supplemented with verbal handover is feasible. It resulted in a significant improvement in surrogate markers of patient care quality.